INFLUENCE OF USE OF MIND MAPPING METHOD BY TEACHERS ON TEACHING PREPARATION IN BASIC SCHOOL IN SUBJECT OF MATERIALS TEACHING EYES LESSON SCIENCE NATURAL SCIENCE (IPA) - Dadang Hermansyah; Ramdhan Witarsa (PrimaryEdu : Journal of Primary Education, 2017)
In terms of time, Mind Mapping can streamline the use of time in studying an information. This is mainly because this method can present a comprehensive picture of a thing in a short time. In other words, Mind Mapping is able to cut learning time by changing the pattern of linear recording into effective recording and at the same time directly understood by the individual. So is the preparation of teachers. Teaching preparation is a special tip in the successful delivery of a subject matter. One of the subjects in Elementary School (ES) is a Natural Science that in fact many proofs between theory and practice. Therefore, the Mind Mapping method in preparation for teaching is one of the special tips for the delivery of the material in its entirety. The more mature the preparation of a teacher in planning the lesson, the better prepared the teacher teaches. With Mind Mapping, the teacher must have tried to think about the things involved with the lesson to be conveyed, such as the tool of the demonstration, how to estimate the condition of the learning condition if using the props, how to use the props, or whether the learner should try the props We make / we serve. With Mind Mapping, teachers are ready to teach with all their abilities accompanied by learning tools that are prepared. Keywords: Mind Mapping, Preparation, Teaching.